Bibliometric analysis of scholarly publications related to family medicine in Thailand - Nutchar Wiwatkunupakarn; Sasiwimon Moonkayaow; Abigail Morse; Nida Buawangpong; Suphawita Pliannuom; Soe Sandi Tint; Apichai Wattanapisit; Chaisiri Angkurawaranon (Heliyon)
Background: Family medicine has been recognized as a medical specialty in Thailand. However, there is a lack of information about scholarly publications. Bibliometric analysis is a valuable methodology for identifying research trends and knowledge gaps in this field. This study aims to analyze scholarly publications related to family medicine in Thailand. Method: This bibliometric analysis was conducted based on the PubMed search in March 2023. All relevant literature related to 'family medicine' and 'Thailand' was retrieved. Performance analysis examined the publication trends from 1963 to 2023, the top 10 journals publishing relevant articles, and the number of publications by research areas. Science mapping depicted clusters of co-occurring author keywords, their relationships, and the research themes' trend over two decades. Results: A total of 1483 publications were retrieved. The number of publications showed an upward trend, increasing from 61 before 2000 to 359 in 2020. The Journal of the Medical Association of Thailand was the leading journal, publishing 267 articles (18.0 %). Research areas were categorized into Basic Knowledge (n = 211), Clinical Problem Solving (n = 714), Health Service (n = 256), Health System (n = 254), and Medical Education (n = 48). Science mapping identified six clusters based on 106 co-occurrence keywords, including public health, health services, medical issues in older adults, healthcare access, epidemiology, and others. Research themes have shifted from infectious diseases and public health to primary care and non-communicable diseases. Conclusion: Future research should focus more on implementation at a population level and healthcare system, with more investigation into geriatric care and child and maternal health.